BOXER OR BANDIT: THE ETHICAL IMAGE OF THE FIGHTING BODY IN THE HOLOCAUST LITERATURE - Wolski, Paweł (Porównania, 2018)
The author compares two versions of the tale by Moshé Garbarz - a boxer-prisoner of various Nazi death and concentration camps. The first one is an autobiographical account, the other a novel. The context of the comparison is the ethical imaginary evoked by the sport of boxing as a cultural phenomenon posited between the natural and the cultural epistemological sphere.